Secondary osteoporosis during long-term steroid treatment - Sewerynek, Ewa; Bajon, Karolina; Stuss, Michał (Menopause Review/Przegląd Menopauzalny, 2007)
Secondary osteoporosis results from bone mass loss, being the effect of certain diseases or other, bone metabolism-affecting factors. In men, it makes up 50% of all osteoporosis cases, while it is more rarely observed in women. Among all the identified causes of secondary osteoporosis, chronic corticotherapy is most often indicated. The loss of bone mass concerns, first of all, the spongy substance of bone, and is more intensive during the initial 6-12 months of treatment. In turn, the degree of bone quality reduction depends on the dose and the time period of administration of glucocorticoids. The effect of steroids on the osseous tissue is complex and results, among others, from disorders in calcium metabolism, reduced activity of sex hormones and from direct effects of glucocorticoids on bone tissue cells. Detailed mechanisms of osteoporosis, induced by steroids, are still unclear, despite many clinical and experimental studies. This report provides the current knowledge regarding post-steroid osteoporosis and effective methods of its treatment.